Vertical transport of anthropogenic lead by reversible scavenging in the South Atlantic Ocean - Olivelli, Arianna; Paul, Maxence; Xu, Hui; Kreissig, Katharina; Coles, Barry J.; Moore, Rebekah E. T.; Bridgestock, Luke; Rijkenberg, Micha; Middag, Rob; Lohan, Maeve C.; Weiss, Dominik J.; Rehkamper, Mark; et al. (Earth and Planetary Science Letters, 2025)
Funding: Arianna Olivelli was supported by the Natural Environment Research Council (NERC) (NE/S007415/1), as were Dominik Weiss, Tina van de Flierdt, and Mark Rehkämper (NE/H006095/1). Maeve Lohan was funded by NERC (NE/H004475/1). The GEOTRACES GA02 section cruises were made possible by the Netherlands Organization for Scientific Research (NWO) project grant 839.08.410. Stable lead (Pb) isotopes have been regarded as tracers of ocean circulation, both in the present time and geological past. Here we present a new dataset of seawater Pb concentrations and isotope compositions for ten depth profiles from the South Atlantic Ocean (GEOTRACES cruises GA02 and GA10). By comparing Pb isotope data collected on the two cruises, and by modelling the distribution of Pb with an extended optimum multiparameter analysis, we find evidence of vertical transport of anthropogenic Pb pollution due to reversible scavenging. Surface to depth transfer of polluted Pb is aided by high suspended particulate matter loads at the Brazil – Malvinas Confluence and along ∼40°S in the South Atlantic. Overall, our findings caution the use of Pb isotope ratios as ventilation tracers in the South Atlantic and emphasize the importance of particle-seawater interaction for biogeochemical cycles. Peer reviewed